2014
DOI: 10.1016/j.jvs.2014.04.041
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and impact of undiagnosed cognitive impairment in older vascular surgical patients

Abstract: The prevalence of cognitive impairment among older patients presenting for vascular surgery is high and frequently undiagnosed before admission. It is feasible to use the MoCA to identify cognitive impairment in this high-risk surgical group preoperatively. The combined assessment of frailty and cognition is predictive of adverse postoperative outcomes and longer LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 49 publications
1
105
0
1
Order By: Relevance
“…Care delivery to patients with dementia in acute hospitals has advanced under the spotlight that was attracted by examples of detrimental care [21, 24]. The evidence shows that cognitive impairments must be actively identified for appropriate management to be undertaken [2528]. Studies [26, 28, 29] have shown that cognitive impairment is under-detected, and that lack of detection is linked to poorer care.…”
Section: Recognition Of the Needmentioning
confidence: 99%
“…Care delivery to patients with dementia in acute hospitals has advanced under the spotlight that was attracted by examples of detrimental care [21, 24]. The evidence shows that cognitive impairments must be actively identified for appropriate management to be undertaken [2528]. Studies [26, 28, 29] have shown that cognitive impairment is under-detected, and that lack of detection is linked to poorer care.…”
Section: Recognition Of the Needmentioning
confidence: 99%
“…In a prospective study using the Montreal Cognitive Assessment (MoCA) test to assess mild CI in elderly patients undergoing elective surgery, Na and Yy demonstrated the prevalence of mild CI to be 56% with an associative increase with age (9). In another prospective study of 114 elderly patients undergoing vascular surgery, Partridge et al showed that 68% of patients met the criteria for CI or dementia (10). Similarly, in a prospective study of 129 elderly patients who underwent lumbar spinal surgery, Lee et al found the prevalence of CI to be 38% using the Mini-Mental Status Examination (1).…”
Section: Discussionmentioning
confidence: 99%
“…However, surgeons have little knowledge of the assessment and management of preoperatively identifiable age-related factors that affect outcomes. Frailty, poor functional status, cognitive impairment and postoperative delirium in older people have all been shown to be associated with prolonged postoperative stay, adverse postoperative outcomes, [13][14][15][16][17] and postoperative discharge to a higher level of care. 18 The prevalence and severity of postoperative complications in an older surgical patient has also been shown to have a negative effect on the time take to return to baseline functional status.…”
Section: Preoperative Carementioning
confidence: 99%